2018
DOI: 10.1088/1361-6528/aabbd6
|View full text |Cite
|
Sign up to set email alerts
|

Dopant radial inhomogeneity in Mg-doped GaN nanowires

Abstract: Using atom probe tomography, it is demonstrated that Mg doping of GaN nanowires grown by Molecular Beam Epitaxy results in a marked radial inhomogeneity, namely a higher Mg content in the periphery of the nanowires. This spatial inhomogeneity is attributed to a preferential incorporation of Mg through the m-plane sidewalls of nanowires and is related to the formation of a Mg-rich surface which is stabilized by hydrogen. This is further supported by Raman spectroscopy experiments which give evidence of Mg-H com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 41 publications
(62 reference statements)
2
24
2
Order By: Relevance
“…However, in absence of In, the amount of incorporated Mg atoms in AlN NWs was negligible, which was assigned to both the size of Mg and its tendency to segregate on the surface, similar to what is found in the case of GaN layers [80]. In absence of In co-doping when growing the upper AlN NW section in the present case, it can be concluded that the enhanced lateral nucleation probability responsible for the formation of the AlN nanotubes is indeed associated with the surface segregation of Mg. Studies on the Mg doping of GaN NWs have put in evidence a preferential Mg incorporation through the sidewalls, due to the stabilization of a Mg-H reconstruction on the m-plane [81,82]. The present data indeed suggest that a similar mechanism could be effective in the case of AlN, with the consequence of stabilizing the Mg-rich outer layer of AlN and enhancing the sidewall nucleation probability.…”
Section: Growth Of Aln Nanotubessupporting
confidence: 67%
“…However, in absence of In, the amount of incorporated Mg atoms in AlN NWs was negligible, which was assigned to both the size of Mg and its tendency to segregate on the surface, similar to what is found in the case of GaN layers [80]. In absence of In co-doping when growing the upper AlN NW section in the present case, it can be concluded that the enhanced lateral nucleation probability responsible for the formation of the AlN nanotubes is indeed associated with the surface segregation of Mg. Studies on the Mg doping of GaN NWs have put in evidence a preferential Mg incorporation through the sidewalls, due to the stabilization of a Mg-H reconstruction on the m-plane [81,82]. The present data indeed suggest that a similar mechanism could be effective in the case of AlN, with the consequence of stabilizing the Mg-rich outer layer of AlN and enhancing the sidewall nucleation probability.…”
Section: Growth Of Aln Nanotubessupporting
confidence: 67%
“…The Si concentration profile is shown in (e). (a,b) Reproduced with permission from ref . Copyright 2018 IOP Publishing.…”
Section: Iii-nitride Nanowire Materials and Devicesmentioning
confidence: 99%
“…However, this is not necessarily the case for NWs. As a matter of fact, it has been found that GaN NWs obeyed a specific doping regime, with a Si solubility limit higher than in layers 25 and an incorporation mechanism of Mg favouring its accumulation in NWs periphery 9,26 . Indeed in the case of InN NWs, first principle calculation have demonstrated that the formation energy of substitutional Mg is lowered close to the surface, which has been assigned to an eased elastic strain relaxation related to the large amount of free surface in NWs 27 .…”
mentioning
confidence: 99%